2000
DOI: 10.1002/1522-2624(200012)163:6<577::aid-jpln577>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Selenium adsorption in soils as influenced by different anions

Abstract: Studies on selenium adsorption were conducted on seleniferous and non‐seleniferous soils of north‐west India. Soils were equilibrated with graded levels of Se ranging from 1 to 100 μg ml—1 tagged with 75Se in the presence of sulphate, nitrate and phosphate ions, generally being applied to soils as inorganic fertilizers. The adsorption of Se on different soils, both in the presence and absence of competing anions, increased with increase in the level of Se added. Adsorption of Se conformed to Langmuir equation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
4
26
0
2
Order By: Relevance
“…Increased Se availability was observed in the incubation experiment where an addition of sulphate significantly increased the extractability of selenate added to the soils. A similar result was found by Dhillon and Dhillon (2000), where the addition of sulphate as gypsum decreased the retention of Se in soils. This enhanced selenate extractability could explain the increased Se uptake from Se fertiliser by S addition in Experiment 1, where the soil effect may dominate over the plant physiological effect because the crop was not deficient in S. The enhanced selenate extractability may occur as a result of decreased selenate adsorption by the soil minerals in the presence of sulphate.…”
Section: Selenium Fertilisation Of Wheat Increased Se Concentrations supporting
confidence: 85%
See 1 more Smart Citation
“…Increased Se availability was observed in the incubation experiment where an addition of sulphate significantly increased the extractability of selenate added to the soils. A similar result was found by Dhillon and Dhillon (2000), where the addition of sulphate as gypsum decreased the retention of Se in soils. This enhanced selenate extractability could explain the increased Se uptake from Se fertiliser by S addition in Experiment 1, where the soil effect may dominate over the plant physiological effect because the crop was not deficient in S. The enhanced selenate extractability may occur as a result of decreased selenate adsorption by the soil minerals in the presence of sulphate.…”
Section: Selenium Fertilisation Of Wheat Increased Se Concentrations supporting
confidence: 85%
“…Indeed, selenite has been found to be the dominant Se species in UK arable field soils (Stroud et al 2009), and in wheat field trials before and after selenate fertilisation . Sulphate added to soil may decrease selenate adsorption (Dhillon and Dhillon 2000) or suppress microbial uptake and assimilation of selenate (Lindblow-Kull et al 1985;Zehr and Oremland 1987). These effects could result in enhanced availability of selenate fertiliser for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…While not as much studied as the interaction of sulfate and selenate, some studies confirm an antagonistic effect of phosphate on selenite uptake in plants (Hopper and Parker, 1999;Broyer et al, 1972), whereas others found little effect (Mora et al, 2008;Nakamaru and Sekine, 2008;Yläranta, 1990b). However, phosphate may reduce selenite adsorption on soil solid surfaces due to competition for binding sites, since it is more strongly adsorbed than selenite, and thus make Se more plant-available (Barrow et al, 2005;Dhillon and Dhillon, 2000;Yläranta, 1983). Still, an addition of phosphate did not significantly increase leaching of selenite from clay, sandy loam, or Carex peat in a study by Yläranta (1991) which could be expected if selenite was adsorbed to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of Se in soils is a function of sorption and desorption of Se. Both sorption and desorption of Se are, in turn, determined mainly by the soil pH, redox potential, microbial activity, mineralogy, soil organic matter, and other anions such as phosphate, sulphate, oxalate, and molybdate for adsorption sites (Dhillon and Dhillon, 2000;Goh and Lim, 2004). Selenite is sorbed more strongly than selenate onto clays, but not as strongly as phosphate or fluoride (Barrow and Whelan, 1989).…”
Section: -3mentioning
confidence: 99%